Systematic Review of Drilling Problems and Their Solutions in Petroleum Engineering - M. Nasir Bashir; Muhammad Nihal Naseer; M. M. Quazi; M Saif Wakeel; Imran Ali; Manzoore Elahi M Soudagar; Jahanzeb Bhatti (Journal of ICT, Design, Engineering and Technological Science, 2021)
The difficulty in drilling arises due to unexpected and surprising behavior of rocks which leads to waste of time, cost, material and sometimes whole borehole. The logging becomes difficult to perform and to investigate due to drilling issues such as borehole instability, lost circulation stuck pipe and under gauge holes. This study sheds light on the state of art of drilling problems, affiliated issues and causes along with their best possible prediction, prevention and solution methodologies. The well schedule, weekly drilling report, construction document, and different well documents were thoroughly inspected. This study incorporates the benefits of statistical analysis of 20 wells, including lateral longitudinal and vertical, as well as how effective constitutive modeling is for classifying well-bore instability triggers and forecasting safe mud-weight windows. The detection models discussed encourages superior comprehension of the fundamental material science standards, and gives improved situational consciousness of drilling problems’ occurrences.